LIMNOLOGICAL STUDIES OF TANDA AND CHANDRAPRABHA RESERVOIRS - SINGH, B. K.; SRIVASTAVA, KALPANA; SINGH, H. P. (Journal of the Inland Fisheries Society of India, 2022)
Uttar Pradesh has 1.37 lakhs ha of reservoir area of which small reservoirs contribute to a total area of 20845 ha (Sugunan, 1995). Small reservoirs offer scope for better production than medium and large reservoirs. Though created basically for irrigation or power, this source has tremendous scope for fish production (Paul and Sugunan, 1990) because of its vast magnitude and prevalence of lotic as well as lentic conditions. This study was conducted in two reservoirs of eastern Uttar Pradesh, Tanda and Chandraprabha during different seasons (summer, monsoon and winter) in 2003-05. Chandraprabha reservoir is situated in district Chanduali on the river Chandraprabha with water spread area of 1038 ha.and mean depth of 6.5 m. whereas Tanda reservoir is locatedÂ on river Khajuri in district Mirzapur having a water spread area of 712 ha. and mean depth of 3.3 m.